Administrative Reforms: A Paradigm Shift through Public Vigilantism: Empowering the Public through Administrative Reforms and Vigilantism (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the wake of recent developments and people’s participation, the administrator needs to have new traits of tact, programmatic approach, dynamism, flexibility and adaptability in any situation. Vigilant public opinion guarding the rights of the individuals and the community is must. Public shall be adequately informed about the mattes in which government action directly impinges on their daily lives. The community should have the knowledge of administrative norms and reforms, practices and structures then only they can provide genuine support for the goals, policies and programmes of the government. Public vigilantism through RTI is increasingly becoming a powerful tool to promote, transparency and corruption free administration. Whistle Blower Act, focusing on Public Interest Disclosure now play an active role in unearthing illegal and unethical practices going on in any organization. Lokpal Bill first passed in 1968 is still fighting to make its way towards Jan lokpal bill